Shotgun proteomic profiling of dormant, 'non-culturable' Mycobacterium tuberculosis - Nikitushkin, Vadim; Shleeva, Margarita; Loginov, Dmitry; Dyčka F, Filip; Sterba, Jan; Kaprelyants, Arseny (PloS one, 2022)
Dormant cells of Mycobacterium tuberculosis, in addition to low metabolic activity and a high level of drug resistance, are characterized by 'non-culturability'-a specific reversible state of the inability of the cells to grow on solid media. The biochemical characterization of this physiological state of the pathogen is only superficial, pending clarification of the metabolic processes that may exist in such cells. In this study, applying LC-MS proteomic profiling, we report the analysis of proteins accumulated in dormant, 'non-culturable' M. tuberculosis cells in an in vitro model of self-acidification of mycobacteria in the post-stationary phase, simulating the in vivo persistence conditions-the raw data are available via ProteomeXchange with identifier PXD028849. This approach revealed the preservation of 1379 proteins in cells after 5 months of storage in dormancy; among them, 468 proteins were statistically different from those in the actively growing cells and bore a positive fold change (FC). Differential analysis revealed the proteins of the pH-dependent regulatory system PhoP and allowed the reconstruction of the reactions of central carbon/glycerol metabolism, as well as revealing the salvaged pathways of mycothiol and UMP biosynthesis, establishing the cohort of survival enzymes of dormancy. The annotated pathways mirror the adaptation of the mycobacterial metabolic machinery to life within lipid-rich macrophages: especially the involvement of the methyl citrate and glyoxylate pathways. Thus, the current in vitro model of M. tuberculosis self-acidification reflects the biochemical adaptation of these bacteria to persistence in vivo. Comparative analysis with published proteins displaying antigenic properties makes it possible to distinguish immunoreactive proteins among the proteins bearing a positive FC in dormancy, which may include specific antigens of latent tuberculosis. Additionally, the biotransformatory enzymes (oxidoreductases and hydrolases) capable of prodrug activation and stored up in the dormant state were annotated. These findings may potentially lead to the discovery of immunodiagnostic tests for early latent tuberculosis and trigger the discovery of efficient drugs/prodrugs with potency against non-replicating, dormant populations of mycobacteria.
Keywords: Latent Tuberculosis; Mycobacterium tuberculosis; Proteomics; latentní tuberkulóza; Humans; proteomika; Mass Spectrometry; tuberkulóza lymfatických uzlin; Tuberculosis, Lymph Node; hmotnostní spektrometrie; lidé